Plant Hormones in Phytoplasma Infected Plants - Dermastia, Marina (Frontiers in Plant Science, 2019)
Phytoplasmas are bacterial plant pathogens that need a plant host and an insect vector for their spread and survival. In plants, the physiological responses that phytoplasmas trigger result in symptom development through effects on hormonal, nutritional, and stress signaling pathways, and the interactions between these. In this review, recent advances on the involvement of plant hormones together with their known and deduced roles in plants infected with phytoplasmas are discussed. Several studies have directly, or in many cases indirectly, addressed plant hormone systems in phytoplasma-infected plants. These have provided accumulating evidence that phytoplasmas extensively affect plant hormone pathways. Phytoplasmas thus, with disturbing complex plant hormone networks, suppress plant immunity and modify plant structure, while optimizing their nutrient acquisition and facilitating their colonization of the plants, and their dissemination among plants by their insect vectors.